(untitled) (Tempo e Argumento, 2009)
The PRT-ERP was one of Argentina’s main guerrilla organizations between 1969 and 1977. Due to their clandestine nature, a problem found in the analysis of these groups was to define who joined it and why. This is particularly complicated due to the scarcity of available hard data. This study seeks to answer who the PRT-ERP militants were, where they came from, what their family and work background was, what their process of politicization was, and why they joined this specific organization. As such, the study seeks to reconstruct life histories of several hundred PRT guerrillas. This effort is based on a variety of sources including party documentation, and dozens of interviews with former militants.